The effect of decongestion on nasal airway patency and airflow - Xiao, Qiwei (Sci Rep, 2021)
Nasal decongestant reduces blood flow to the nasal turbinates, reducing tissue volume and increasing nasal airway patency. This study maps the changes in nasal anatomy and measures how these changes affect nasal resistance, flow partitioning between superior and inferior cavity, flow patterns and wall shear stress. High-resolution MRI was applied to capture nasal anatomy in 10 healthy subjects before and after application of a topical decongestant. Computational fluid dynamics simulated nasal airflow at steady inspiratory flow rates of 15 L.min[Formula: see text] and 30 L.min[Formula: see text]. The results show decongestion mainly increases the cross-sectional area in the turbinate region and SAVR is reduced (median approximately 40[Formula: see text] reduction) in middle and lower parts of the cavity. Decongestion reduces nasal resistance by 50[Formula: see text] on average, while in the posterior cavity, nasal resistance decreases by a median factor of approximately 3 after decongestion. We also find decongestant regularises nasal airflow and alters the partitioning of flow, significantly decreasing flow through the superior portions of the nasal cavity. By comparing nasal anatomies and airflow in their normal state with that when pharmacologically decongested, this study provides data for a broad range of anatomy and airflow conditions, which may help characterize the extent of nasal variability.